Measuring Customer Engagement in Social Media: The Uncovered Practice of SMEs in Malaysia - Md Jani, Noraniza; Zakaria, Mohd Hafiz; Maksom, Zulisman; M. Haniff, Md. Shariff (Journal of Advanced Computing Technology and Application (JACTA), 2020)
Contemporary marketing metaphors focus on customers in the brand community, hence measuring customer response on social media websites is positioned as an influential agenda for businesses. Measuring customer engagement in the cyber world can provide prerequisite signals for small businesses looking for long-term stability. However, previous studies and industry reports indicate a lack of valuable facts about measuring customer engagement as a result of social media efforts after advertising and campaign posts. This paper addresses the shortcomings by conducting a study for SMEs to identify approaches to measure customers and prospects on the branded sites they currently practice. The method conducted was a quantitative survey to uncover the measurement practice of 125 SMEs in selected states of Malaysia. At the post-descriptive analysis, the studied items have produced new and meaningful information on social media usage trends and their measurement initiatives. The current findings are discussed and expected to contribute to the knowledge base within the social media domain and industry players. Finally, two recommendations have generated; first, to support the progress of a similar study in the future and second, to forward the facts to the relevant authorities.